Comparative Analysis Of Cost Calculation With Activity-Based Costing And Traditional Methods - Emmuel Prayer Waruwu; Basram Pratama Sitanggang; Petrus Irwando Simatupang; Jeremy Togar Sitorus; Hamonangan Siallagan (Jurnal Multidisiplin Sahombu, 2024)
In the modern business world, accurate cost calculation is crucial for effective decision-making. Traditional methods often fail to reflect actual resource consumption, leading to inaccurate pricing and resource allocation. This research aims to analyze the use of Activity-Based Costing (ABC) and compare it with traditional methods. The research approach is qualitative, employing literature review methods. The findings show that ABC, which allocates costs based on activities performed, provides more realistic and accurate cost estimates. ABC helps companies identify non-value-added activities, improve efficiency, and reduce waste. Although ABC is more complex and expensive to implement, it provides more precise cost information, supporting optimal decision-making regarding pricing, product strategy, and resource allocation. Conversely, traditional methods are simpler but often result in less accurate cost allocation and do not reflect variations in activity consumption. Therefore, ABC is superior in terms of accuracy and effectiveness in identifying waste and inefficient activities, despite requiring technological support and higher initial costs.